Wealth and sexual behaviour among men in Zimbabwe - Musiyarira, Shepstone (My University, 2012)
INTRODUCTION: Zimbabwe has witnessed a decline in HIV prevalence in the general population estimated to be 27% in 2001, 19% in 2005, 16% in 2007 and 14% in 2009 (Mapingure et al., 2010). Whilst it is a notable decline the rate is still high. Sexual behaviour change has been reported as key to this HIV prevalence decline. Partner reduction has been advocated as an important strategy in HIV prevention. Understanding the socioeconomic and demographic factors influencing the sexual behaviours that are either sustaining the declining, yet still high, prevalence rates is critical to inform interventions. There is growing interest in the association between individual’s socioeconomic status and sexual risk taking behaviour in sub-Saharan Africa. The general objective was to examine the association between wealth and sexual behaviour among men in Zimbabwe. METHOD: Analysis of data from 7175 sexually active aged 15-54 years who participated in the Zimbabwe’s 2005/06 Demographic and Health Survey was done using logistic regression models and have reported odds ratios (OR) with Confidence intervals. In the multiple logistic regressions, two models were used. Model 1 included variables: wealth, age and education whilst in model 2 we controlled for: marital status, type of residence, region of residence and religion because these socio-demographic factors influence male sexual behaviour. The dependent variables included: unprotected sex at last encounter, multiple and concurrent sexual partnerships in last 12 months. RESULTS: When we controlled for potential confounding effects of education, age, marital status, type of residence, region of residence and religion, men in the middle wealth category of the population were less likely to have engaged in unprotected sex in the last encounter with a nonspousal cohabiting partner (OR 0.41, 95% CI 0.22 to 0.76). Wealth was found to be not statistically significantly associated with multiple and concurrent sexual partnerships. CONCLUSION: Wealthy men in Zimbabwe are less likely to engage in unprotected sex. Wealth’s association with multiple and concurrent sexual partnerships was not confirmed in this study. Equitable distribution of wealth and sound economic policies are critical in improving the general welfare of nationals so as to reduce or eliminate some of the factors that cloud the associations between socioeconomic and demographic factors and sexual behaviours of individuals. Policies and programs that recommend deferral of gratification remain critical in order to reduce number of partners.
M.A. Faculty of Humanties, School of Social Sciences. University of the Witwatersrand, 2011
Keywords: Wealth; Sexual behaviour; Multiple and concurrent sexual partnerships